Adverse childhood experiences and late-life diurnal HPA axis activity: Associations of different childhood adversity types and interaction with timing in a sample of older East Prussian World War II refugees - Maier, Bernhard; Zillich, Lea; Streit, Fabian; Wildenberg, Katharina; Rietschel, Marcella; Hammes, Hans-Peter; Witt, Stephanie; Deuschle, Michael (Psychoneuroendocrinology, 2022)
Adverse childhood experiences (ACEs) have been associated with unfavorable health outcomes throughout the life up to old age. Mechanisms through which ACEs impact later life health are still not entirely clear. There is growing evidence for the idea that alterations in the hypothalamic pituitary adrenal (HPA) axis might cause the effects of ACEs on later health consequences. Only few studies have investigated associations between ACEs and diurnal HPA axis functioning in older adults. Therefore, we investigated the impact of type and timing of ACEs linked to flight of war on diurnal HPA axis activity in a sample of East Prussian World War II refugees aged 74-91 years. We calculated a dichotomous variable according to the (minimum) age at trauma: early ACE (eACE; 0-5 years) and late ACE (lACE; 6-17 years). Multiple linear regression analysis using different ACEs linked to flight of war (war-related trauma, individual experience of violence, neglect) as well as age at trauma and the interactions of ACEs and age at trauma as predictors and three cortisol outcomes (AUCG (area under the curve with respect to the ground), decline (morning to night) and CAR (cortisol awakening response)) was performed. For AUCG, we found a negative association of individual experience of violence only in lACE participants. For decline, a positive association with neglect was observed for the whole study sample. The overall model for CAR was not statistically significant. Our findings support the hypothesis that type as well as timing of ACEs might influence diurnal HPA axis functioning into old age. These findings may contribute to a better understanding of the lifelong influence of ACEs.